Absorption of Lead and Mercury in Dominant Aquatic Macrophytes of Balili River and Its Implication to Phytoremediation of Water Bodies - Jones T. Napaldet; Inocencio E. Buot Jr (Tropical Life Sciences Research, 2020)
In the Philippines, phytoremediation studies on heavy metals are mainly concentrated in mining areas amidst several reports of heavy metal contamination even in non-mining sites in various parts of the country. Such was the case Balili River which was reportedly contaminated with mercury (Hg) and lead (Pb). Aquatic macrophytes growing in the river could offer the solution to this problem via phytoremediation. Thus, this study was conceptualised to determine the uptake of Hg and Pb in selected dominant macrophytes of the river namely Amaranthus spinosus, Eleusine indica and Pennisetum purpureum. Soil, water and plant samples gathered from the study sites were submitted to Department of Science and Technology-Cordillera Administrative Region (DOST-CAR) laboratory for Hg and Pb determination. Soil and wastewater of Balili River were found contaminated with Pb but not with Hg. The soil recorded higher Hg concentration than water while Pb concentrations did not differ between the two media. The aquatic macrophytes in the study registered consistently higher Hg and Pb in their shoots > roots but differed in their capacities and distribution in the shoot organs. Hg and Pb accumulation was significantly (p = 0.00) higher in stem of P. purpureum while in E. indica, leaf had the highest accumulation, though not statistically significant (p = 0.09). For A. spinosus, Hg was highest in its leaf while Pb in stem, though not statistically significant (p = 0.06). Among the three macrophytes, P. purpureum showed the highest potential for Hg uptake and translocation and for Pb uptake. On the other hand, the highest Pb internal transfer was recorded in E. indica. These results contradict initial findings that Pb is mostly accumulated in plant roots with minimal shoot translocation. Also, these results show that local macrophytes in Balili River, even if obnoxious weeds, are ecologically important and could be used for phytoremediation of local rivers that are recipient of small-scale mine tailings.